Singabantu - a journey to self determination - Mafu, Thubelihle (Centre for Film and Media Studies, 2023)
Zimbabwe, from pre-colonial times to date, has always been viewed as a divided nation. From the onset people were divided according to tribal lines with the Ndebele and Shona tribes dominating the narrative. History of the Ndebele people depicts them as settlers who came from the present-day South Africa and incorporated other tribes on the way to form a Ndebele nation. However, these so-called settlers settled in a place which is now known as present day Matabeleland. Colonialization exacerbated these divisions and although the natives somewhat united during the war of liberation, the divisions continued to manifest after independence. Gukurahundi, which saw to the killings of people in Matabeleland further aggravated the situation and to date there have been outcries that the people of Matabeleland who are predominantly Ndebele are marginalised. The project is based on a blog, Singabantu- A journey to self-determination that seeks to understand how activists view the Matabeleland question and this will ultimately contribute to the digital archiving of these stories that are not adequately covered in the mainstream media. The project seeks to understand perceptions of these activists 40 years after independence and how they envision an ideal Zimbabwe.